Communities of Practice and Vintage Innovation A Strategic Reaction to Technological Change - Schiavone, Francesco; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book focuses on the notion of (3z(Bvintage innovation(3y (Band its application in various old technology-based communities of practice. Some communities of practice resist and react to technological change by adopting new technological products ((3z(Bvintage products(3y(B) that extend the lifetime of their old, favored products and practices. There are a number of potential reasons for such strategic reactions, which are analyzed by the author. The book opens by reviewing the nature of technological change. Old technology-based communities of practice and their typical reactions to technological change are then discussed, and the concept of vintage innovation, introduced and explained. The book presents four case studies of communities of users in which vintage innovation emerged: analog photographers, radio amateurs, arcade videogame players, and disc jockeys.s
1 Technological change -- 2 Communities of practice -- 3 Vintage innovation -- 4 Vintage innovation by firms -- 5 Vintage innovation by users .
Keywords: Economics; Marketing; Economics/Management Science; Innovation/Technology Management; R & D/Technology Policy; Marketing; Organizational Studies, Economic Sociology